Causes and risk factors for death in infants with congenital chylothorax - Kubo, Yuichi; Ibara, Satoshi; Tokuhisa, Takuya; Kibe, Masaya; Sueyoshi, Kazuyoshi; Kamitomo, Masato; Kato, Motoi (Frontiers in Pediatrics, 2025)
AimTo identify mortality risk factors in infants with congenital chylothorax (CC) and analyze the causes of death, including pathological examination.MethodsFor this single-center retrospective study, we included 27 patients with CC. We divided them into the ALIVE and the DEAD groups, with the DEAD group subdivided into the Early-DEAD group and the Late-DEAD group to compare patient characteristics and risk factors using robust statistical methods. Causes of death were reviewed, including pathological findings from autopsies.ResultsThe mortality rate was 44% (12 of 27 infants, with 15 survivors). Univariate analysis showed associations between mortality and chromosomal abnormalities and fetal ascites. A longer duration of hydrothorax in utero was specifically associated with early neonatal death. Multivariate regression analysis identified fetal ascites as the strongest independent predictor of mortality. Pathological examination of six autopsied fatal cases revealed lymphangiectasia, including systemic lymphangiectasia in all five whole-body autopsies.ConclusionPoor prognosis in infants with CC is strongly associated with fetal ascites, which we hypothesize serves as a key clinical marker for underlying Generalized Lymphatic Dysplasia (GLD). This systemic lymphatic disorder, identified pathologically as lymphangiectasia in fatal cases, may be the primary driver of mortality. Chromosomal abnormalities appear to be a significant predisposing factor for this severe phenotype.